The Effect Of Thermal Activation Time and Type Of Fly Ash On The Compressive Strength Of High Volume Fly Ash-Bamboo Mortar - S. Hamzah; E. Aprianti (International Association of Lowland Technology, 2019)
A growing number of concrete productions per year will lead to increase manufactured cement significantly. Bamboo is one of the main materials from agriculture, it has many function particularly in the field of agriculture. This research is including waste materials origin from bamboo. The methodology used are curing in a hot water after 24 h and curing at the room temperature. The compressive strength is equal to the mortar containing 100% cement. Thermal activation then following air curing (HAC) is the effective way to produce a denser microstructure of mortar containing cementitious materials and consequently to achieve the higher compressive strength with lower water absorption.